IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PELAYANAN SISTEM IZIN TERPADU DI KABUPATEN LOMBOK TENGAH - Hasyim Asyari (Universitas 45 Surabaya, 2022)
In order to provide excellent service through the fields of licensing which would also refer to the legal rules in force in Indonesia as well as regulations established by the Government itself through the Regional Rules and Regulations of Central Lombok regent. Write this in the discussion of the basis of government policy, mechanism of licensing services, factors that support and hinder the implementation of an integrated permit system services with used a normative-empirical legal research, method of approach, regulatory approach, Conceptual Approach, Empirical Approaches, Writing discusses the basis of government policy Referring to laws and regulations determined by the government, Central Lombok Regency Regional Regulations, Regent's Regulations. The Licensing Service Procedure refers to central Lombok Regent Regulation No. 13 of 2011 as well as supporting factors and inhibitory factors.